COMPARATIVE ANALYSIS OF DENTAL CEMENTS FROM INORGANIC MATERIALS - Radu Mircea Sireteanu-Cucui; Alina Stefanache; Clara Haddad; Laura Ecaterina Romila; Gabriela Calin; Dana Mihai; Gabriela Turcu; Pogăcian-Maier Alexandra Camelia (Romanian Society of Oral Rehabilitation, 2024)
Aim of the Study: This study aims to provide a comprehensive comparison of different inorganic dental cements by reviewing existing literature, discussing their properties, applications, and advancements, and outlining future prospects in this field. Introduction: Dental cements play a critical role in restorative dentistry, providing essential properties like adhesion, biocompatibility, and mechanical strength necessary for the success and longevity of dental restorations. Among the inorganic dental cements, zinc phosphate, glass ionomer, and resin-modified glass ionomer cements are widely used due to their distinct advantages and specific applications. Methods and Materials: A thorough literature review was conducted, analyzing peer-reviewed studies and clinical reports on zinc phosphate, glass ionomer, and resin-modified glass ionomer cements. The analysis focused on comparing their chemical compositions, mechanical properties, adhesion capabilities, biocompatibility, and clinical performance. Results: Zinc phosphate cement is noted for its high compressive strength but lacks adhesion to tooth structures and can cause postoperative sensitivity. Glass ionomer cement offers fluoride release and good adhesion but has lower mechanical strength. Resin-modified glass ionomer cement combines the benefits of both, providing enhanced mechanical properties, moisture resistance, and fluoride release. Conclusions: Inorganic dental cements each present unique benefits and limitations. Zinc phosphate is best for its mechanical strength, glass ionomer for caries prevention, and resin-modified glass ionomer for a balanced performance. Future advancements in nanotechnology and adhesive formulations promise further improvements in dental cement properties, enhancing restorative dentistry outcomes.